Evaluation of a 5‐Tier Scheme Proposed for Classification of Sequence Variants Using Bioinformatic and Splicing Assay Data: Inter‐Reviewer Variability and Promotion of Minimum Reporting Guidelines. Issue 10 (13th August 2013) - Walker, Logan C.; Whiley, Phillip J.; Houdayer, Claude; Hansen, Thomas V. O.; Vega, Ana; Santamarina, Marta; Blanco, Ana; Fachal, Laura; Southey, Melissa C.; Lafferty, Alan; Colombo, Mara; De Vecchi, Giovanna; et al.
ABSTRACT Splicing assays are commonly undertaken in the clinical setting to assess the clinical relevance of sequence variants in disease predisposition genes. A 5‐tier classification system incorporating both bioinformatic and splicing assay information was previously proposed as a method to provide consistent clinical classification of such variants. Members of the ENIGMA Consortium Splicing Working Group undertook a study to assess the applicability of the scheme to published assay results, and the consistency of classifications across multiple reviewers. Splicing assay data were identified for 235 BRCA1 and 176 BRCA2 unique variants, from 77 publications. At least six independent reviewers from research and/or clinical settings comprehensively examined splicing assay methods and data reported for 22 variant assays of 21 variants in four publications, and classified the variants using the 5‐tier classification scheme. Inconsistencies in variant classification occurred between reviewers for 17 of the variant assays. These could be attributed to a combination of ambiguity in presentation of the classification criteria, differences in interpretation of the data provided, nonstandardized reporting of results, and the lack of quantitative data for the aberrant transcripts. We propose suggestions for minimum reporting guidelines for splicing assays, and improvements to the 5‐tier splicing classification system to allow future evaluation of its performance as a clinical tool.